2018
DOI: 10.1016/j.ccell.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Viruses as Antigen-Agnostic Cancer Vaccines

Abstract: Selective destruction of neoplastic tissues by oncolytic viruses (OVs) leads to antigen-agnostic boosting of neoantigen-specific cytotoxic T lymphocyte (CTL) responses, making OVs ideal companions for checkpoint blockade therapy. Here we discuss the mechanisms whereby OVs modulate both adjuvanticity and antigenicity of tumor cells. Suppression of antitumor immunity after OV therapy has not been observed, possibly because viral antigen expression diminishes as the antiviral response matures, thereby progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
169
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 82 publications
1
169
0
3
Order By: Relevance
“…In earlier studies from our groups and others, oncolytic viruses were armed with immune stimuli, such as heat shock proteins, chemokines, and cytokines, to activate antitumor immune responses 19,20,[47][48][49][50][51][52] . However, oncolytic virus therapies so far only showed limited efficacy in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies from our groups and others, oncolytic viruses were armed with immune stimuli, such as heat shock proteins, chemokines, and cytokines, to activate antitumor immune responses 19,20,[47][48][49][50][51][52] . However, oncolytic virus therapies so far only showed limited efficacy in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neoantigen-specific T cells can be activated by comprehensive sequencing and the identification of individual mutations, the computational prediction of neoantigen epitopes, and vaccination with neoantigen epitopes for each patient [16][17][18] . In contrast to this cumbersome strategy, oncolytic viruses possess the potential to offer a simpler in situ vaccination approach to activate T cell responses by locoregional immune activation, immunogenic oncolytic tumor cell death, mutant neoantigen release and presentation, and alteration of the immunosuppressive tumor microenvironment 19,20 . Recent clinical trials demonstrated that oncolytic virotherapy with talimogene laherparepvec (T-Vec), a genetically modified granulocytemacrophage colony-stimulating factor (GM-CSF)-expressing herpes simplex virus, promoted intratumoral T cell infiltration and improved anti-PD-1 or CTLA immunotherapy 21,22 .…”
mentioning
confidence: 99%
“…Oncolytic viruses have been proposed as a novel class of anticancer therapy, and viruses with different backbones and transgenes are currently being evaluated in clinical trials (15)(16)(17). Although the success of oncolytic viruses was initially predicted during the past decade based on their faster replication and enhanced oncolytic capability, they are now beginning to be recognized as an immunotherapeutic because the strongest and most durable responses after oncolytic virotherapy are coupled with successful induction of antitumor immunity with increased tumor-specific effector and memory T cells (16,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Measles vaccines are oncolytic, i.e., they preferentially replicate in malignant cells compared to normal cells, eventually resulting in selective tumor cell lysis. By releasing tumor antigens in concert with DAMPs (danger-associated molecular patterns) and PAMPs (pathogen-associated molecular patterns) during viral infection, oncolytic virotherapy acts as an antigen-agnostic in situ tumor vaccine [12]. While the herpes virus talimogene laherparepvec has been approved by the FDA and EMA, several other oncolytic viruses are currently in clinical trials, including vaccinia, adeno-, rhabdo-and reoviruses [13].…”
Section: Introductionmentioning
confidence: 99%
“…While the herpes virus talimogene laherparepvec has been approved by the FDA and EMA, several other oncolytic viruses are currently in clinical trials, including vaccinia, adeno-, rhabdo-and reoviruses [13]. Oncolytic measles vaccines are under clinical investigation for treatment of several tumor entities, and early trials have indicated the safety and efficacy of this approach [12]. The advantages of oncolytic measles vaccines include the well documented safety record, genomic stability, and the versatility of the reverse genetics system [2,14,15].…”
Section: Introductionmentioning
confidence: 99%